FACTORS INFLUENCING RESIDENTIAL LAND PRICES IN TIEN DU DISTRICT, BAC NINH PROVINCE - Dinh Hai, Le; Thi Huong, Nguyen (Journal of Forestry Science and Technology, 2017)
Land pricing has an increasing importance due to strong growth of the real estate market in Vietnam in the last years. In that respect, a permanent preoccupation for specialists is to find better methods to evaluate the real estates, especially residential land. In the international practice, the current methods for land pricing are statistical and econometric models. The main aim of this paper is to establish and use multiple linear regression models in order to identify factors that significantly affect the price of residential land in Tien Du district, Bac Ninh province. In this study, we collected data from 100 transections of residential land in Tien Du district, Bac Ninh province. By using IBM SPSS Statistics 23 and applying multiple linear regression for data analyses, we found that there are 4 key factors, including: Location, Distance to Central Business District (CBD), Width of facade, and Security, significantly affect prices of residential land in the study area. The findings of this research, therefore, provide implications for solution development, with the aims being to manage, regulate and stabilize the residential land prices in Tien Du district, Bac Ninh province.